High-dispersity cobalt-based Fischer-Tropsch synthesis catalyst as well as preparation method and application thereof
Through step-by-step precipitation method and the use of modified support, the challenges of Co-based Fischer-Tropsch synthesis catalyst in the dispersion and stability of active metals were solved, and a cobalt-based Fischer-Tropsch synthesis catalyst with high dispersion and good stability was prepared, which showed high activity and low inactivation rates when applied to Fischer-Tropsch synthesis reaction.
Patent Information
- Application Number
- CN202311413807.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-27
- Publication Date
- 2025-04-29
AI Technical Summary
The existing Co-based Fischer-Tropsch synthesis catalysts have challenges in the dispersion and stability of active metals, and the cobalt reserves are limited and the price is high, making it difficult to develop catalysts with high cobalt dispersion and stability.
The cobalt-based Fischer-Tropsch synthesis catalyst was prepared by step-by-step precipitation method. Through the precipitation process and aging treatment, the modification additive SiO2 or Al2O3 modified TiO2 is used as a support to achieve high dispersion and uniform particle size distribution of the active component cobalt.
The prepared catalyst has good uniformity, high dispersion of active component cobalt and concentrated particle size distribution, moderate interaction force between active metal and support, and is not prone to sintering and cobalt surface coating during Fischer-Tropsch synthesis reaction, and has high activity and good stability.
Smart Images

Figure CN119897122A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of Fischer-Tropsch synthesis catalysts, and in particular relates to a highly dispersed cobalt-based Fischer-Tropsch synthesis catalyst and a preparation method and application thereof. Background Art
[0002] Since the advent of Fischer-Tropsch synthesis, the active components of the catalysts used are mainly transition metals such as Fe, Co, Ni and Ru. Among them, the catalytic hydrogenation activity of Ni-based catalysts is too strong, and its hydrogenation reaction product is mainly CH4; Ru-based catalysts have high low-temperature hydrogenation activity, and the reaction products are mainly long-chain hydrocarbons. They are more suitable catalysts for Fischer-Tropsch synthesis, but factors such as small global reserves and high prices have prevented them from being used in large-scale production. Combining product distribution, production feasibility and economy, the most suitable active metal components in Fischer-Tropsch synthesis catalysts are Fe and Co.
[0003] Compared with iron-based Fischer-Tropsch synthesis catalysts, Co-based Fischer-Tropsch synthesis catalysts have outstanding advantages such as high activity, weak water-gas shift reaction, heavy hydrocarbon selectivity, high carbon utilization and long life, and have become a research hotspot for FT synthesis catalysts. However, cobalt reserves are limited and the price is high, so it is particularly important to develop cobalt-based catalysts with high cobalt dispersion and good stability.
[0004] Patent document CN104368343B discloses a method for preparing a cobalt-based Fischer-Tropsch synthesis catalyst with controllable and monodisperse particles, which uses a mesoporous material with a special morphology as a carrier, and uses anhydrous ethanol, distilled water, and a carboxyl organic compound as a solvent to dissolve the active component, while controlling the ratio between the three, and then controlling the flow rate added dropwise to the mesoporous material, and finally drying and roasting. The catalyst cobalt particle size prepared by this patent is controllable and monodisperse, with high dispersion, and is applied in the Fischer-Tropsch synthesis reaction with the characteristics of high reaction activity, good stability, high heavy hydrocarbon selectivity, low methane selectivity, and not easy to sinter. However, this method is only applicable to the case where mesoporous silica foam materials, mesoporous alumina foam materials, mesoporous carbon foam materials, SBA-16 molecular sieves, etc. with foamy or cage-like three-dimensional structures are carriers, and the catalyst preparation process is complicated.
[0005] Patent document AU2009229706B2 discloses that the use of silicon dioxide whose surface is treated with zirconium-phosphorus as a carrier can improve the dispersion and reduction degree of the active component cobalt, and can prevent the deactivation of the catalyst by inhibiting cobalt sintering during the reaction. However, this method is only applicable to silicon oxide systems. If this method is used to treat aluminum oxide systems or titanium oxide systems, the specific surface area of the carrier will decrease, thereby reducing the dispersion of cobalt and the activity of the catalyst.
[0006] Metal atoms with high dispersion move and aggregate due to high surface energy, resulting in poor stability. It is challenging to achieve both high dispersion of catalyst active metals and catalyst stability at the same time in this field. Summary of the invention
[0007] The purpose of the present invention is to provide a highly dispersible cobalt-based Fischer-Tropsch synthesis catalyst and a preparation method and application thereof, in view of the problems of active metal dispersion and stability of existing Co-based Fischer-Tropsch synthesis catalysts. A precipitation preparation process is adopted to ensure that the obtained catalyst has good uniformity, high dispersion of the active component cobalt and a relatively concentrated particle size distribution, moderate interaction between the active metal and the carrier, and is not prone to sintering or cobalt surface coating during the application of the catalyst to the Fischer-Tropsch synthesis reaction. The catalyst has high activity and good stability when used in the Fischer-Tropsch synthesis reaction.
[0008] In order to achieve the above object, the present invention provides the following technical solutions:
[0009] In a first aspect, a method for preparing a highly dispersible cobalt-based Fischer-Tropsch synthesis catalyst is provided, comprising the following steps:
[0010] (1) contacting a mixed solution containing a titanium precursor and a modification aid precursor with an alkaline precipitant to perform a precipitation reaction, and performing an aging treatment to obtain a precipitate I; washing the obtained precipitate I, and dispersing it in deionized water to obtain a modified carrier suspension;
[0011] Wherein, the modification auxiliary agent precursor is a silicon precursor and / or an aluminum precursor;
[0012] (2) adding a mixed solution containing a cobalt precursor and an auxiliary agent precursor and an alkaline precipitant to the suspension prepared as above to carry out a precipitation reaction, and performing an aging treatment to obtain a precipitate II; washing, filtering, drying, and calcining the precipitate II to obtain a cobalt-based Fischer-Tropsch synthesis catalyst;
[0013] Wherein, the auxiliary agent precursor is one or more of a manganese precursor, a cerium precursor and a lanthanum precursor.
[0014] A solution containing a titanium precursor and a solution containing a modifying aid precursor can be prepared separately, and then the two can be mixed to form a mixed solution; alternatively, a mixed solution containing a titanium precursor and a modifying aid precursor can be prepared in advance. According to the preparation method provided by the present invention, in some embodiments, the concentration of the mixed solution containing a titanium precursor and a modifying aid precursor is 1.0-4 mol / L (for example, 1.5 mol / L, 2.0 mol / L, 2.5 mol / L, 3.0 mol / L, 3.5 mol / L).
[0015] A solution containing a cobalt precursor and a solution containing an auxiliary agent precursor may be prepared separately, and then the two may be mixed to form a mixed solution; alternatively, a mixed solution containing a cobalt precursor and an auxiliary agent precursor may be prepared in advance. In some embodiments, the mixed solution containing a cobalt precursor and an auxiliary agent precursor has a concentration of 1.0-3 mol / L (e.g., 1.5 mol / L, 2.0 mol / L, 2.5 mol / L).
[0016] In some embodiments, in step (1), the ratio of titanium precursor:modification aid precursor is 1:(0.005-0.3), for example, 1:0.006, 1:0.008, 1:0.01, 1:0.02, 1:0.04, 1:0.05, 1:0.1, 1:0.15, 1:0.2, 1:0.25.
[0017] In some embodiments, in step (2), the ratio of cobalt precursor: auxiliary agent precursor: titanium precursor is (0.4-3): (0.001-0.3): 1. For example, based on 1 mol of titanium precursor, the amount of cobalt precursor can be 0.4 mol, 0.5 mol, 0.6 mol, 0.8 mol, 1.0 mol, 1.5 mol, 2.0 mol, 2.5 mol, and the amount of auxiliary agent precursor can be 0.002 mol, 0.004 mol, 0.005 mol, 0.008 mol, 0.01 mol, 0.02 mol, 0.05 mol, 0.1 mol, 0.15 mol, 0.2 mol, 0.25 mol.
[0018] In some embodiments, the concentration of the alkaline precipitant is 1.0-4.0 mol / L (eg, 1.5 mol / L, 2.0 mol / L, 2.5 mol / L, 3.0 mol / L, 3.5 mol / L).
[0019] In some embodiments, the alkaline precipitant is selected from at least one of sodium hydroxide solution, sodium carbonate solution, aqueous ammonia, ammonium carbonate solution, ammonium bicarbonate solution and potassium carbonate solution.
[0020] In some embodiments, in step (1) and step (2), the alkaline precipitating agents are the same or different.
[0021] In some embodiments, the amount of the alkaline precipitant used is determined according to the pH value required for the precipitation environment, and the amounts of the alkaline precipitant used in step (1) and step (2) are the same or different.
[0022] In some embodiments, the titanium precursor is selected from one or more of metatitanic acid, tetrabutyl titanate and titanium tetrachloride.
[0023] In some embodiments, the silicon precursor is selected from at least one of tetrabutyl silicate and silica sol.
[0024] In some embodiments, the aluminum precursor is selected from one or more of aluminum nitrate, aluminum chloride and aluminum sol.
[0025] In some embodiments, the cobalt precursor is selected from one or more of cobalt nitrate, cobalt carbonate, cobalt acetate and cobalt chloride.
[0026] In some embodiments, the manganese precursor is a soluble salt of manganese, for example, manganese nitrate and its hydrate, manganese chloride, manganese sulfate;
[0027] In some embodiments, the cerium precursor is a soluble salt of cerium, for example, cerium nitrate, cerium chloride;
[0028] In some embodiments, the lanthanum precursor is a soluble salt of lanthanum, such as lanthanum nitrate, lanthanum acetate, or lanthanum carbonate.
[0029] In some embodiments, in the precipitation reaction of step (1), the pH of the system is controlled to be 6.0-9.0 (e.g., 6.5, 7.0, 7.5, 8.0, 8.5), and the temperature of the precipitation reaction is 40-90°C (e.g., 45°C, 50°C, 60°C, 80°C, 85°C).
[0030] In some embodiments, the process conditions of the aging treatment in step (1) include: an aging temperature of 40-90°C (for example, 45°C, 50°C, 60°C, 80°C, 85°C), a control system pH of 6.0-9.0 (for example, 6.5, 7.0, 7.5, 8.0, 8.5), and an aging time of 4-12 hours (for example, 5 hours, 6 hours, 8 hours, 10 hours).
[0031] In some embodiments, in the precipitation reaction of step (2), the pH of the system is controlled to be 7.5-10.0 (e.g., 8.0, 8.5, 9.0, 9.5), and the temperature of the deposition precipitation reaction is 40-90°C (e.g., 45°C, 50°C, 60°C, 80°C, 85°C).
[0032] In some embodiments, the process conditions of the aging treatment in step (2) include: an aging temperature of 40-90°C (for example, 45°C, 50°C, 60°C, 80°C, 85°C), a control system pH of 7.5-10.0 (for example, 8.0, 8.5, 9.0, 9.5), and an aging time of 4-12 hours (for example, 5 hours, 6 hours, 8 hours, 10 hours).
[0033] In some embodiments, the process conditions of the aging treatment in step (1) and step (2) are the same or different.
[0034] In some embodiments, the drying process conditions include: a drying temperature of 60-150°C (e.g., 65°C, 80°C, 100°C, 120°C, 140°C), and a drying time of 2-48h (e.g., 3h, 5h, 10h, 15h, 20h, 28h, 32h, 40h).
[0035] In some embodiments, the calcination process conditions include: a calcination temperature of 350-700°C (e.g., 400°C, 450°C, 500°C, 600°C, 650°C), and a calcination time of 2-48h (e.g., 3h, 5h, 10h, 15h, 20h, 28h, 32h, 40h).
[0036] In a second aspect, a highly dispersible cobalt-based Fischer-Tropsch synthesis catalyst is provided, wherein the carrier of the catalyst is a TiO2 carrier modified by a modification aid SiO2 or Al2O3;
[0037] The cobalt-based Fischer-Tropsch synthesis catalyst comprises the following components, based on the weight of the catalyst:
[0038] 15%-45wt% (e.g., 18wt%, 20wt%, 22wt%, 24wt%, 25wt%, 30wt%, 35wt%, 38wt%, 40wt%) of active ingredient cobalt (e.g., calculated as element),
[0039] 0.05%-5wt% (e.g., 0.08wt%, 0.1wt%, 0.2wt%, 0.5wt%, 0.6wt%, 0.8wt%, 1.0wt%, 2.0wt%, 4.0wt%) of auxiliary agent components (e.g., calculated as elements),
[0040] 0.5%-5wt% (e.g., 0.6wt%, 0.8wt%, 1wt%, 1.2wt%, 1.5wt%, 2wt%, 2.5wt%, 3.0wt%, 3.2wt%, 3.4wt%, 3.5wt%, 4.0wt%) of modification aid SiO2 or Al2O3,
[0041] The remaining content is TiO2 carrier;
[0042] Wherein, the auxiliary agent component is selected from one or more of manganese, cerium and lanthanum;
[0043] In some embodiments, the cobalt-based Fischer-Tropsch synthesis catalyst is prepared by the preparation method described above. In some embodiments, in the catalyst preparation method, the amount of each raw material component can be calculated based on the content range of each component in the catalyst product.
[0044] In a third aspect, there is provided a cobalt-based Fischer-Tropsch synthesis catalyst prepared by the preparation method described above or use of the cobalt-based Fischer-Tropsch synthesis catalyst described above in a Fischer-Tropsch synthesis reaction.
[0045] The operating steps, process conditions and reaction apparatus of the Fischer-Tropsch synthesis reaction may be conventional choices in the art and will not be described in detail here.
[0046] In the present invention, step-by-step precipitation is adopted, and the TiO2 carrier is first modified by a precipitation process and SiO2 or Al2O3 is selected, and the interaction force between the modified TiO2 carrier and the active metal is suitable, and the active component and the auxiliary component are further dispersed on the modified carrier by a precipitation process, and the obtained catalyst has good uniformity, and the active component cobalt has high dispersibility and a relatively concentrated particle size distribution. That is, the dispersibility of the active component cobalt and the catalyst stability are effectively improved by the step-by-step precipitation process.
[0047] The catalyst of the present invention is prepared by a step-by-step precipitation method. By adopting the above formula and controlling the process conditions in the step-by-step precipitation, the prepared catalyst has good uniformity, the active component cobalt has high dispersibility and the particle size distribution is relatively concentrated, the interaction force between the active metal and the carrier is moderate, the catalyst is not prone to sintering and cobalt surface coating during the Fischer-Tropsch synthesis reaction, and has the advantages of high activity and good stability during the Fischer-Tropsch synthesis reaction. In addition, the preparation method of the present invention has the advantages of simple preparation process, good repeatability, and easy industrial amplification. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 A schematic diagram of the particle size distribution of the catalyst obtained in Example 1 is shown;
[0049] Figure 2 A schematic diagram of the particle size distribution of the catalyst obtained in Comparative Example 1 is shown. DETAILED DESCRIPTION
[0050] In order to understand the technical features and content of the present invention in detail, the preferred embodiments of the present invention will be described in more detail below. Although the preferred embodiments of the present invention are described in the embodiments, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments described herein. For those who do not specify specific conditions in the embodiments, they are carried out according to normal conditions or the conditions recommended by the manufacturer.
[0051] <Source of raw materials>
[0052] In the following examples and comparative examples, the sources of some reagents or raw materials used, without specifying the manufacturer, are all conventional products that can be purchased commercially.
[0053] Example 1
[0054] (1) 59.2 g of titanium tetrachloride was weighed and dissolved in 300 g of water, and 4.1 g of tetrabutyl silicate was dissolved in 50 g of ethanol, and the titanium precursor solution and the silicon precursor solution were mixed to prepare a mixed solution containing a titanium precursor and a silicon precursor;
[0055] Weigh 50g of deionized water into a large beaker, and add the prepared mixed solution and 3.0mol / L ammonia water to the large beaker in parallel to perform precipitation reaction. Adjust the pH value of the system to 7.5 by adding ammonia water, control the temperature to 60°C, and then age for 4 hours under this condition to obtain a precipitate; then wash the obtained precipitate with deionized water for several times, and then disperse it in a large beaker with deionized water to obtain a suspension;
[0056] (2) 41.6 g of cobalt nitrate (hexahydrate) and 2.0 g of 50 wt% manganese nitrate solution were dissolved in 50 g of water to obtain a mixed solution containing a cobalt precursor and an auxiliary manganese precursor. The mixed solution and 3.0 mol / L ammonia water were added dropwise to the large beaker containing the suspension in step (1) to carry out a precipitation reaction. The pH value was adjusted to 8.5 by adding ammonia water, the temperature was controlled to 60°C, and then aged under this condition for 4 hours. After obtaining the precipitate, it was washed with deionized water several times, filtered, and then dried at 120°C for 10 hours, and then calcined at 600°C for 3 hours to obtain a cobalt-based Fischer-Tropsch synthesis catalyst A1.
[0057] Based on the total weight of the catalyst, the content of SiO2 is 3.4wt%.
[0058] Embodiment 2:
[0059] The preparation steps of the cobalt-based Fischer-Tropsch synthesis catalyst refer to Example 1, except that the amount of tetrabutyl silicate added in step (1) is changed to 1.73 g; the remaining steps are the same as Example 1.
[0060] A cobalt-based Fischer-Tropsch synthesis catalyst A2 was obtained.
[0061] Based on the total weight of the catalyst, the content of SiO2 is 1.2wt%.
[0062] Embodiment 3:
[0063] The preparation steps of the cobalt-based Fischer-Tropsch synthesis catalyst refer to Example 1, except that in step (1), 4.1 g of tetrabutyl silicate is replaced with 1.20 g of aluminum nitrate (Al(NO3)·9H2O); the remaining steps are the same as Example 1.
[0064] A cobalt-based Fischer-Tropsch synthesis catalyst A3 was obtained.
[0065] Based on the total weight of the catalyst, the content of Al2O3 is 0.7wt%.
[0066] Embodiment 4:
[0067] The preparation steps of the cobalt-based Fischer-Tropsch synthesis catalyst refer to Example 1, except that the amount of the 50 wt % manganese nitrate solution in step (2) is changed to 11.4 g; the remaining steps are the same as Example 1.
[0068] A cobalt-based Fischer-Tropsch synthesis catalyst A4 was prepared.
[0069] Embodiment 5:
[0070] The preparation steps of the cobalt-based Fischer-Tropsch synthesis catalyst refer to Example 1, except that in step (2), 2.0 g of 50 wt% manganese nitrate solution is replaced by 0.30 g of lanthanum nitrate (La(NO3)·6H2O); the remaining steps are the same as Example 1.
[0071] A cobalt-based Fischer-Tropsch synthesis catalyst A5 was prepared.
[0072] Embodiment 6:
[0073] The preparation steps of the cobalt-based Fischer-Tropsch synthesis catalyst refer to Example 1, except that the amount of cobalt nitrate (hexahydrate) in step (2) is changed to 100 g; the remaining steps are the same as Example 1.
[0074] A cobalt-based Fischer-Tropsch synthesis catalyst A6 was prepared.
[0075] Embodiment 7:
[0076] The preparation steps of the cobalt-based Fischer-Tropsch synthesis catalyst are similar to those of Example 1, except that in step (1), the pH of the system is controlled at 6.5.
[0077] A cobalt-based Fischer-Tropsch synthesis catalyst A7 was prepared.
[0078] Comparative Example 1:
[0079] (1) Weigh 25.0 g of titanium dioxide and 1.0 g of silicon dioxide and mix them evenly to obtain a mixed carrier;
[0080] (2) 40.1 g of cobalt nitrate (hexahydrate) and 1.5 g of 50 wt% manganese nitrate solution were dissolved in 30 g of water to obtain a mixed solution containing a cobalt precursor and a manganese precursor as an auxiliary agent. The mixed solution was added dropwise to the mixed carrier obtained in step (1), and after impregnation for 4 hours, it was dried at 120°C for 10 hours, and then calcined at 600°C for 3 hours to obtain catalyst B1.
[0081] Comparative Example 2:
[0082] The preparation process of the catalyst refers to the impregnation method in Comparative Example 1, except that in step (1), 25.0 g of titanium dioxide and 1.0 g of aluminum oxide are weighed and mixed evenly to obtain a composite carrier; the operation of step (2) is the same as that of Comparative Example 1.
[0083] Finally, catalyst B2 was obtained.
[0084] Comparative Example 3:
[0085] 59.2 g of titanium tetrachloride was weighed and dissolved in 300 g of water, and 4.1 g of tetrabutyl silicate was dissolved in 50 g of ethanol, and the titanium precursor solution and the silicon precursor solution were mixed to prepare a mixed solution I containing a titanium precursor and a silicon precursor; 41.6 g of cobalt nitrate (hexahydrate) and 2.0 g of a 50 wt% manganese nitrate solution were dissolved in 50 g of water to obtain a mixed solution II containing a cobalt precursor and an auxiliary manganese precursor; the mixed solution I was mixed with the mixed solution II to obtain a mixed solution III;
[0086] Weigh 100 g of deionized water into a large beaker, and add the prepared mixed solution III and 3.0 mol / L ammonia water into the beaker in parallel. Adjust the pH value of the system to 8.5, control the temperature to 60°C, and age under this condition for 4 hours to obtain a precipitate. Wash it with deionized water several times, filter it, and then dry it at 120°C for 10 hours. Then, calcine it at 600°C for 3 hours to obtain a cobalt-based Fischer-Tropsch synthesis catalyst B3.
[0087] Based on the total weight of the catalyst, the content of SiO2 is 2.3wt%.
[0088] Test Example 1: Catalytic Performance Evaluation of Catalyst
[0089] Evaluation method: 0.5 g of the catalyst prepared in the above embodiments and comparative examples was taken and loaded into a fixed bed reactor. First, it was reduced for 12 h in a H2 atmosphere, at a space velocity of 8000 ml / g / h, at normal pressure and at a temperature of 300°C. Then, the reducing gas was switched to the reaction gas for reaction. The reaction conditions were: raw material reaction gas group H2 / CO / N2=66 / 33 / 1, space velocity of 3200 ml / g / h, pressure of 2 MPa, temperature of 215-220°C, and the CO conversion rate of the reaction for 10 h and 110 h was measured respectively, and the deactivation rate D was calculated:
[0090] D = (CO conversion rate (10h) - CO conversion rate (110h)) / 100h.
[0091] Table 1 Composition of catalysts obtained in various embodiments and comparative examples
[0092]
[0093] Table 2 Characterization of the catalysts obtained in each embodiment and comparative example
[0094]
[0095] Table 3 Evaluation results of catalyst performance obtained in various examples and comparative examples
[0096]
[0097] The composition of the catalysts prepared in each embodiment and comparative example is shown in Table 1. It can be seen from the results in Tables 2-3 that each embodiment adopts a step-by-step precipitation process, firstly through a precipitation process and selecting SiO2 or Al2O3 to modify the TiO2 carrier in this process, and controlling the amount of SiO2 or Al2O3, the interaction force between the modified TiO2 carrier and the active metal is appropriate, and on this basis, further through a precipitation process and selecting appropriate process conditions in this process, the active component and the auxiliary component are evenly dispersed on the modified carrier, the obtained catalyst has good uniformity, the active component cobalt has high dispersibility and a small particle size, and the particle size distribution is relatively concentrated (for example, comparative example). Figure 1 and Figure 2 The prepared catalyst is not prone to sintering and cobalt surface coating defects during the Fischer-Tropsch synthesis reaction, and has the advantages of high activity, low deactivation rate and good stability during the Fischer-Tropsch synthesis reaction.
[0098] Comparative Documents 1-2 use an impregnation method, and Comparative Document 3 uses a co-precipitation process. The particle size of the active component in the resulting catalyst is relatively large, and the catalyst is prone to sintering and cobalt surface coating defects during the Fischer-Tropsch synthesis reaction, which will have an adverse effect on the catalyst's activity and stability (low carbon dioxide conversion rate, high methane selectivity, and increased catalyst deactivation rate).
[0099] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those skilled in the art without departing from the spirit of the present invention.
Claims
1. A method for preparing a highly dispersible cobalt-based Fischer-Tropsch synthesis catalyst, characterized in that: The steps include: (1) contacting a mixed solution containing a titanium precursor and a modification aid precursor with an alkaline precipitant to perform a precipitation reaction, and performing an aging treatment to obtain a precipitate I; washing the obtained precipitate I, and dispersing it in deionized water to obtain a modified carrier suspension; Wherein, the modification auxiliary agent precursor is a silicon precursor and / or an aluminum precursor; (2) adding a mixed solution containing a cobalt precursor and an auxiliary agent precursor and an alkaline precipitant to the suspension prepared as above to carry out a precipitation reaction, and performing an aging treatment to obtain a precipitate II; washing, filtering, drying, and calcining the precipitate II to obtain a cobalt-based Fischer-Tropsch synthesis catalyst; Wherein, the auxiliary agent precursor is one or more of a manganese precursor, a cerium precursor and a lanthanum precursor.
2. The preparation method according to claim 1, characterized in that: The mixed solution containing the titanium precursor and the modification aid precursor has a concentration of 1.0-4 mol / L; and / or The mixed solution containing the cobalt precursor and the auxiliary agent precursor has a concentration of 1.0-3 mol / L.
3. The preparation method according to claim 1 or 2, characterized in that: In step (1), the ratio of titanium precursor to modification aid precursor is 1:(0.005-0.3); In step (2), the ratio of cobalt precursor: auxiliary agent precursor: titanium precursor is (0.4-3): (0.001-0.3):
1.
4. The preparation method according to any one of claims 1 to 3, characterized in that The concentration of the alkaline precipitant is 1.0-4.0 mol / L; The alkaline precipitant is selected from at least one of sodium hydroxide solution, sodium carbonate solution, aqueous ammonia, ammonium carbonate solution, ammonium bicarbonate solution and potassium carbonate solution.
5. The preparation method according to any one of claims 1 to 4, characterized in that: In step (1) and step (2), the alkaline precipitating agents are the same or different; The amount of the alkaline precipitant used is determined according to the pH value required for the precipitation environment. The amounts of the alkaline precipitant used in step (1) and step (2) are the same or different.
6. The preparation method according to any one of claims 1 to 5, characterized in that: The titanium precursor is selected from one or more of metatitanic acid, tetrabutyl titanate and titanium tetrachloride; The silicon precursor is selected from at least one of tetrabutyl silicate and silica sol; The aluminum precursor is selected from one or more of aluminum nitrate, aluminum chloride and aluminum sol; The cobalt precursor is selected from one or more of cobalt nitrate, cobalt carbonate, cobalt acetate and cobalt chloride; The manganese precursor is a soluble salt of manganese; The cerium precursor is a soluble salt of cerium; The lanthanum precursor is a soluble salt of lanthanum.
7. The preparation method according to any one of claims 1 to 6, characterized in that In the precipitation reaction of step (1), the pH of the system is controlled to be 6.0-9.0, and the temperature of the precipitation reaction is 40-90° C.; and / or The process conditions of the aging treatment in step (1) include: an aging temperature of 40-90° C., a pH value of the control system of 6.0-9.0, and an aging time of 4-12 hours; and / or In the precipitation reaction of step (2), the pH of the system is controlled to be 7.5-10.0, and the temperature of the sedimentation reaction is 40-90° C.; and / or The process conditions of the aging treatment in step (2) include: an aging temperature of 40-90° C., a pH value of the control system of 7.5-10.0, and an aging time of 4-12 hours; Preferably, the process conditions of the aging treatment in step (1) and step (2) are the same or different.
8. The preparation method according to any one of claims 1 to 7, characterized in that: The drying process conditions include: drying temperature of 60-150° C., drying time of 2-48 h; and / or The calcination process conditions include: a calcination temperature of 350-700° C. and a calcination time of 2-48 hours.
9. A highly dispersible cobalt-based Fischer-Tropsch synthesis catalyst, characterized in that: The catalyst carrier is a TiO2 carrier modified by a modification aid SiO2 or Al2O3; The cobalt-based Fischer-Tropsch synthesis catalyst comprises the following components, based on the weight of the catalyst: 15%-45wt% of active ingredient cobalt, 0.05%-5wt% of auxiliary components, 0.5%-5wt% of modified additive SiO2 or Al2O3, The remaining content is TiO2 carrier; Wherein, the auxiliary agent component is selected from one or more of manganese, cerium and lanthanum; Preferably, the cobalt-based Fischer-Tropsch synthesis catalyst is prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the cobalt-based Fischer-Tropsch synthesis catalyst prepared by the preparation method according to any one of claims 1 to 8 or the cobalt-based Fischer-Tropsch synthesis catalyst according to claim 9 in a Fischer-Tropsch synthesis reaction.
Citation Information
Patent Citations
Cobalt / zirconium-phosphorus / silica catalyst for Fischer-Tropsch synthesis and method of preparing the same
AU2009229706B2
A preparation method of a particle-controllable and monodisperse cobalt-based Fischer-Tropsch synthesis catalyst
CN104368343B